Production of charged pions, kaons, and protons in e+e- annihilations into hadrons at √s=10.54 GeV - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
Inclusive production cross sections of π±, K± and p/¯p per hadronic e+e− annihilation event are measured at a center-of-mass energy of 10.54 GeV, using a relatively small sample of very high quality data from the BABAR experiment at the PEP-II B-factory at the SLAC National Accelerator Laboratory. The drift chamber and Cherenkov detector provide clean samples of identified π±, K±, and p/¯p over a wide range of momenta. Since the center-of-mass energy is below the threshold to produce a B¯¯¯B pair, with B a bottom-quark meson, these data represent a pure e+e−→q¯q sample with four quark flavors, and are used to test QCD predictions and hadronization models. Combined with measurements at other energies, in particular at the Z0 resonance, they also provide precise constraints on the scaling properties of the hadronization process over a wide energy range.
Im Titel ist das Pluszeichen "+" und das Minuszeichen "-" hochgestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 17.11.2021